2018
DOI: 10.1038/s41598-018-34144-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the adsorption of phosphorus in all fractions from sediment by modified maifanite

Abstract: Sediment phosphorus (P) removal is crucial for the control of eutrophication, and the in-situ adsorption is an essential technique. In this study, modified maifanite (MMF) prepared by acidification, alkalization, salinization, calcination and combined modifications, respectively, were first applied to treat sediment P. The morphology and microstructure of MMF samples were characterized by X-ray fluorescence (XRF), Fourier transform infrared (FTIR), X-ray diffraction (XRD), scanning electron microscope (SEM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…This may be due to the possible complexes of silver nanoparticles and phosphate. Moreover, at low pH surface hydroxyl groups of AgNPs-TAC were protonated in the ligand exchange process and -OH 2+ was to displace easily from the metal binding sites 44 . Thus, ligand exchange was also one of mechanisms of phosphate adsorption onto AgNPs-TAC.…”
Section: Discussion Of Agnps-tac Role In Phosphate Adsorptionmentioning
confidence: 99%
“…This may be due to the possible complexes of silver nanoparticles and phosphate. Moreover, at low pH surface hydroxyl groups of AgNPs-TAC were protonated in the ligand exchange process and -OH 2+ was to displace easily from the metal binding sites 44 . Thus, ligand exchange was also one of mechanisms of phosphate adsorption onto AgNPs-TAC.…”
Section: Discussion Of Agnps-tac Role In Phosphate Adsorptionmentioning
confidence: 99%
“…In the same way, it has been reported that below 4.5 of pH values the mineral dissolution is favored, promoting the precipitation reactions between H 2 PO 4 − and cations in solution (Al 3+ and Fe 3+ ) [77], and to form H 2 PO 4 − -cation-organic matter complexes [53]. The increase of the H 2 PO 4 − adsorption at a low pH has been demonstrated on pillared bentonites [75], AgNPs-tea activated carbon [76], sediments [78] and in Andisol soils [24]. Future research should be addressed to corroborate whether, in the presence of both ENPs, one of these mechanisms was prevalent for H 2 PO 4 − adsorption on T-OM and R-OM soil samples, or whether several mechanisms acted together.…”
Section: Ad-and Desorption Of Phosphate On Soilsmentioning
confidence: 99%
“…The simulation model for chemical transport and transformation between soil or sediment and runoff is an essential method for studying pollution prediction and migration (Koopmans et al, 2019; Yang et al, 2016; Zhang et al, 2020). The PP transport is a dynamic equilibrium process in the runoff‐sediment system and is controlled by the P adsorption–desorption on sediment particles (Huang et al, 2016; Liu et al, 2018). Sediment adsorbs most of the P in the water, and the raindrop‐driven process will affect the transport of chemicals and the concentration variation (Walter et al, 2007).…”
Section: Introductionmentioning
confidence: 99%